The looks of a winner: beauty, gender and electoral success - Niclas Berggren; Henrik Jordahl; Panu Poutvaara (Institute for the Study of Labor (IZA), 2006)
We study the role of beauty in politics. For the first time, focus is put on differences in how women and men evaluate female and male candidates and how different candidate traits relate to success in real and hypothetical elections. We have collected 16,218 assessments by 2,772 respondents of photos of 1,929 Finnish political candidates. Evaluations of beauty explain success in real elections better than evaluations of competence, intelligence, likability, or trustworthiness. The beauty premium is larger for female candidates, in contrast to findings in previous labor-market studies
Keywords: 330; Ästhetik; Geschlecht; Politiker; Wahlverhalten; Finnland